Introducing Wittgenstein - Heaton, John M. (Icon Books, 1994)
Ludwig Wittgenstein has somehow captured the popular imagination as the modern Socrates, the master of enigmatic logic, the fascinating and attractive icon of modernism. But what did Wittgenstein really say?